Perbandingan Konsumsi Buah Naga Dan Sari Kacang Hijau Terhadap Peningkatan Kadar Hb Pada Ibu Hamil Anemia Di Wilayah Puskesmas Mranggen II Kecamatan Mranggen Kabupaten Demak (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Anemia is still a complex health problem in Indonesian women. Themost common cause of anemia in pregnancy is lack of nutrients in the body.Pharmacological treatment has side effects faster than non-pharmacologicaltreatment. Natural products that are traditionally used as an additional intake in theprevention of anemia, for example there are dragon fruit, green beans, and so on.Purpose: The purpose of this study was to determine the effectiveness comparisonbetween consumption of dragon fruit and mung bean juice on increasing Hb levels inanemia pregnant women in the Mranggen II Public Health Center, Demak Regency.This type of research is quantitative research with a research design using Two GroupPretest Posttest Design. The population in this study were pregnant women withanemia. Sampling using the entire population of as many as 40 respondents. Givingdragon fruit in the form of pieces shows 100% of the ingredients used and green beansare made by boiling to get the juice from the green beans. The research instrumentwas the Easy Touch Hb test as a measuring tool for Hb levels. Data analysis usedPaired T-Test / T-dependent test.Result: The results showed that the average hemoglobin level of pregnant womenwith anemia in the intervention group before being given Dragon Fruit had a Meanvalue of 10.241 g/dl, while after the intervention the Mean value became 11.125 g/dl.The Hb level in the control group before being given Mung Bean Extract had a Meanvalue of 10.825 g/dl while after being given Mung Bean Extract the Mean valuebecame 11.266 g/dl. The results of the statistical test using the Independent T-Testbetween the two intervention groups and the control group showed p-values 0.539which means there is no difference in the effectiveness of giving Dragon Fruit andGreen Bean Extract to increase Hb levels in pregnant women with anemia.Keywords: Dragon fruit, Green Beans, Increased Hb levels, pregnancy